2019
DOI: 10.1111/1759-7714.13214
|View full text |Cite
|
Sign up to set email alerts
|

Comparisons between tumor burden and other prognostic factors that influence survival of patients with non‐small cell lung cancer treated with immune checkpoint inhibitors

Abstract: Background The use of baseline tumor burden (TB) as a prognostic factor for non‐small cell lung cancer (NSCLC) patients treated with immune checkpoint inhibitors (ICIs) and associations between TB and other prognostic biomarkers remain unclear. In this study, we investigated the association between TB and survival in NSCLC patients treated with ICIs in comparison with other biomarkers. Methods We retrospectively evaluated 83 NSCLC patients with ICIs administered between February 2016 and December 2018. TB was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 33 publications
0
12
1
Order By: Relevance
“…Our study also showed that RP was not associated with tumor burden, which is probably because the RECIST v1.1‐defined target lesions do not always truly reflect the entire tumor burden, especially in patients with nonmeasurable disease, such as bone metastases, pleural effusion, or malignant atelectasis. Several studies have also showed that patients with high tumor burden experience poor OS after starting immunotherapy, which suggests that tumor burden may be a prognostic factor rather than a predictor of response …”
Section: Discussionmentioning
confidence: 99%
“…Our study also showed that RP was not associated with tumor burden, which is probably because the RECIST v1.1‐defined target lesions do not always truly reflect the entire tumor burden, especially in patients with nonmeasurable disease, such as bone metastases, pleural effusion, or malignant atelectasis. Several studies have also showed that patients with high tumor burden experience poor OS after starting immunotherapy, which suggests that tumor burden may be a prognostic factor rather than a predictor of response …”
Section: Discussionmentioning
confidence: 99%
“…Tumor response was evaluated using the Response Evaluation Criteria in Solid Tumors version 1.1 [17]. Baseline TB was evaluated using CT for target lesions [13,14]. TB was defined as the sum of the longest diameter for a maximum of five target lesions and up to two lesions per organ [13,14].…”
Section: Treatment Efficacy Evaluation and Assessment Of Baseline Tmentioning
confidence: 99%
“…In all 85 patients, the median values of SUVmax, MTV, and TLG on 18 F-FDG and TB were 6.0 (range, 3.1-21.0), 17.8 cm 3 (range, 1.1-379 cm 3 ), 75.4 gcm 3 /mL (range, 3.9-2550 g•cm 3 /mL), and 65 cm (range, 6.6-230.6 cm), respectively. According to histological types, the median values of SUVmax, MTV, and TLG on 18 F-FDG and TB in adenocarcinoma were 6.7 (range, 3.1-21.3), 11.3 cm 3 (range, 1.1-276 cm 3 ), 58.3 g•cm 3 /mL (range, 3.9-1398 g•cm 3 /mL), and 53 cm (range, 6.6-230.6 cm), respectively, and those in non-adenocarcinoma displayed 8.4 (range, 3.2-20.4) 24.8 cm 3 (range, 1.1-379 cm 3 The discriminative value of various SUVmax, MTV, and TLG cutoffs for 18 F-FDG uptake were explored in the context of OS and PFS ( Figure 2) [13]. For prognosis in OS and PFS analyses, the most discriminative cutoffs based on log-rank test for SUVmax, MTV, and TLG were 6.0, 5.0, and 20, respectively.…”
Section: Assessment Of Suv Max Mtv and Tlg On 18 F-fdg Uptakementioning
confidence: 99%
See 2 more Smart Citations